Analisis Kandungan Timbal (Pb) pada Sedimen di Teluk Totok Kabupaten Minahasa Tenggara - Stanley Klemens Ferdinand Posumah; Sri Seprianto Maddusa; Vennetia Ryckerens Danes (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Lead (Pb) heavy metal contamination in coastal areas adjacent to mining activities poses a serious threat to aquatic ecosystems and public health. This study aimed to analyze Pb content in sediment at Totok Bay, Southeast Minahasa Regency, and assess its compliance with applicable quality standards. A laboratory-based descriptive quantitative study was conducted in November–December 2025 using purposive sampling at 16 coordinate points in Totok Bay waters. Pb concentration was analyzed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) at the Ministry of Health Laboratory (Labkesmas Makassar I), and results were compared against the Australia and New Zealand Guidelines for Fresh and Marine Water Quality (ANZG) with a DGV of 50 mg/kg. Results showed Pb concentrations in sediment ranging from 7.45–53.74 mg/kg, with a mean value of 13.81 mg/kg. Fifteen out of 16 sampling points (93.75%) were below the threshold, while Point 13 recorded 53.74 mg/kg, exceeding the ANZG DGV. Localized contamination at Point 13 was associated with its proximity to mining operations, sand dredging activities, and fine-grained sediment characteristics with higher Pb sorption capacity. This study concludes that Totok Bay has experienced localized Pb contamination requiring continuous environmental monitoring and risk-based coastal management.